2020
DOI: 10.1021/acscatal.9b05225
|View full text |Cite
|
Sign up to set email alerts
|

Pt-Assisted Carbon Remediation of Mo2C Materials for CO Disproportionation

Abstract: Using the CO disproportionation (Boudouard) reaction as a probe reaction, an in-depth analysis of temperature-programmed pulse response data shows that the addition of Pt to Mo 2 C mitigates deactivation of Mo active sites by acting as a carbon collector. CO 2 production on Mo 2 C and Pt/Mo 2 C materials is dependent on both the activation energy and the CO surface concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…The strongest CO 2 binding at a NMC Ni-Ni site (−1.95 eV) is similar to a bidentate CO 2 adsorption configuration on a metallic Mo 2 C nanotube, with a predicted value −2.43 eV at the PBE level and a tridentate configuration of CO 2 adsorption on a CeO 2 (100) surface with an adsorption energy of −1.90 eV at the PBE+U level . All of the strong CO 2 binding energies on these three different materials take place on a stepped surface site.…”
Section: Discussionmentioning
confidence: 92%
“…The strongest CO 2 binding at a NMC Ni-Ni site (−1.95 eV) is similar to a bidentate CO 2 adsorption configuration on a metallic Mo 2 C nanotube, with a predicted value −2.43 eV at the PBE level and a tridentate configuration of CO 2 adsorption on a CeO 2 (100) surface with an adsorption energy of −1.90 eV at the PBE+U level . All of the strong CO 2 binding energies on these three different materials take place on a stepped surface site.…”
Section: Discussionmentioning
confidence: 92%
“…CO dissociation can inevitably cause the carburization of catalysts and the phase transformation in this process, such as from metal oxide to metal carbide, has been frequently observed. 62,66,67 Even on the surface of metal carbides, coke formation can sometimes be a facile process to further aggravate carbon deposition through CO disproportionation ( forward Boudouard reaction: 2CO → CO 2 + C), 11,68 which is an important process in many catalytic reactions. Herein, from the viewpoint of the gas-phase study, we demonstrated that the C 2 ligand in the RhTaC 2 − cluster plays crucial roles in promoting CO 2 reduction and it can directly take part in the reactions through the reverse Boudouard reaction (CO 2 + C → 2CO).…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…The pivotal roles of metal carbide support in regulating the geometrical or electronic structure of the supported precious metals have been frequently emphasized, and the outstanding reactivity of the corresponding catalysts was commonly attributed to the generation of bimetallic carbides at the interfaces. [11][12][13] A fundamental understanding of the nature of these bimetallic carbides and the underlying reaction mechanism is vital to provide scientific guidance for the design of advanced catalysts, but this is a big challenge because this kind of active species evolves rapidly under reaction conditions and carbon deposition makes it more difficult to be characterized.…”
Section: Introductionmentioning
confidence: 99%